Pindar - Pindarus,Gildersleeve, Basil L. (Cambridge University Press, 1885)
Basil L. Gildersleeve (1831-1924) was an American classicist who spent much of his career at Johns Hopkins University. This is his influential 1895 edition of Pindar's Olympian and Pythian Odes, a body of work notable for its insights into lyric poetry and modes of self-understanding. Gildersleeve's remarkable introductory essay outlines Pindar's lineage, patriotism, and poetic development, as well as his poetic themes and structures. It focuses particularly on Pindar's new approach to old themes, his view of government and the human condition, and his role as a conveyer of Greek ethics.
10.1017/CBO9780511698002
Keywords: Pindarus; Olympia; Pythia; Olympic games (Ancient); Athletics